ISOLATION AND IDENTIFICATION OF APIGENIN, A FLAVONOID COMPOUND FROM MACARANGA HYPOLEUCA (REICHB.F. & ZOLL.) - Aisya, Sitti; Megawati, Megawati; Ariani, Novita; Sukirno, Sukirno; Minarti, Minarti; Kurniawan, Hendris Hendarsyah; Hidayat, Arief; Hendra, Medi; Primahana, Gian; Darmawan, Akhmad (BRIN Publishing (Penerbit BRIN), 2024)
The study on Macarang hypolueca (Reichb.f. & Zoll.), which was collected from secondary forests around Samarinda City, East Kalimantan, involved phytochemical investigations that led to the isolation of a flavone type compound of flavonoid from the ethyl acetate fraction. To separate the compounds, silica gel column chromatography was utilized with a gradient solvent system of n-hexane and ethyl acetate, along with the addition of 5%. Infrared analysis (FTIR), mass spectrum (LC-ESI-MS), and nuclear magnetic resonance (1D- and 2D-NMR) were used to identify and elucidate the structure. Based on spectroscopic data and comparison with appropriate references, the isolated compound was identified as apigenin